Untangling the Manganese-α-Synuclein Web - Peres, Tanara Vieira; Parmalee, Nancy L.; Martinez-Finley, Ebany J.; Aschner, Michael (Frontiers in Neuroscience, 2016)
Neurodegenerative diseases affect a significant portion of the aging population. Several lines of evidence suggest a positive association between environmental exposures, which are common and cumulative in a lifetime, and development of neurodegenerative diseases. Environmental or occupational exposure to manganese (Mn) has been implicated in neurodegeneration due to its ability to induce mitochondrial dysfunction, oxidative stress and α-synuclein (α-Syn) aggregation. The role of the α-Syn protein vis-a-vis Mn is controversial, as it seemingly plays a duplicitous role in neuroprotection and neurodegeneration. α-Syn has low affinity for Mn, however an indirect interaction cannot be ruled out. In this review we will examine the current knowledge surrounding the interaction of α-Syn and Mn in neurodegenerative process.